Design of Micro-Controlled Swimming Pool Water Quality Monitoring System with SMS Notification for Educational Purposes with Cost Analysis - Kathryn N. Purazo; Jessa Mae Niña T. Paris; Jan Ilde S. Subaldo; Brian B. Bacal (Universitas Pendidikan Indonesia (UPI), 2024)
This study reported the design of a micro-controlled swimming pool water quality monitoring system with SMS notification, which can be used as a media for the teaching and learning process. We developed to measure and monitor the physical properties of pool water in terms of its pH level, turbidity, and temperature using different sensors to provide water monitoring quality control. As a sample, we showed the data gained from the swimming pools in Tacurong City and Lebak, Sultan Kudarat, the Philippines. A total of thirty-two respondents from the four swimming pools in Tacurong City and Lebak had gathered to participate in this study to evaluate its effectiveness in terms of accuracy in detecting water properties of swimming pools, sending notifications on the schedule of draining, and generating the summary reports of the swimming pool’s water physical properties and schedules of water draining. We also explained the step-by-step design and cost analysis for making this apparatus. The findings of this study suggest the following: (1) to use additional water quality sensors such as microbiological and chemical water parameters that could be utilized with automatic pool monitoring systems, and (2) to have a smart pool chemical monitoring device that utilized water quality sensors that could be easily downloaded and installed on an Android device, and which utilized wireless technology and real-time notifications to monitor the pool water quality.